1994
DOI: 10.2514/3.23750
|View full text |Cite
|
Sign up to set email alerts
|

Motor and plume particle size measurements in solid propellant micromotors

Abstract: Particle size distributions were measured in the chamber, nozzle, and plume of a subscale solid propellant rocket motor. A significant reduction in the mean size of the aluminum/aluminum oxide particles occurred within the motor chamber. The mass fraction of small particles (<2 ft) at the nozzle entrance was less than 10%. Also, most particles were smaller than 50 ft, although a few as large as 85 ft were present. In the converging and throat portions of the nozzle it appeared that particle breakup dominated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The influence of AP size on the agglomeration process of aluminum particles was analyzed by means of windowing engine and SEM, XPS, and XRD by DeLuca [14]. Hovland [5], Laredo et al [15], and Haiqing [16] have used noncontact measurement technology to promote the application and development of laser forward scattering technology in the field of size distribution detection in plume. Weilun et al [17] have used laser forward scattering technology to study the influence of propellant components on the particle size of condensed products.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of AP size on the agglomeration process of aluminum particles was analyzed by means of windowing engine and SEM, XPS, and XRD by DeLuca [14]. Hovland [5], Laredo et al [15], and Haiqing [16] have used noncontact measurement technology to promote the application and development of laser forward scattering technology in the field of size distribution detection in plume. Weilun et al [17] have used laser forward scattering technology to study the influence of propellant components on the particle size of condensed products.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, alumina (Al 2 O 3 ) droplets are generated as one of the combustion products of aluminum droplets. These droplets vary in size from submicrometer to a few hundred micrometers [1][2][3]. It is reasonable to expect that such droplets with different sizes will collide with one another when they are accelerated at different rates, which is what tends to occur in rocket nozzles and in complex evolving geometries, such as star grains.…”
Section: Introductionmentioning
confidence: 99%
“…As an important initial parameter for two-phase numerical calculation, the size distribution of droplets in a combustion chamber is understood well [1][2][3]. However, only a few studies on droplet collision in a solid rocket motor have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Optical techniques for measuring molten aluminum sizes and/or velocities have included point-wise phase Doppler anemometry [4], line-of-sight laser diffraction [5], videography [6], shadowgraphy [7], Schlieren [8], and holography [9]. Among these techniques, imagingbased methods (videography, shadowgraphy, Schlieren, and holography) are particularly advantageous because images allow for differentiation of reacting aluminum drops from other particulates and provide insight into the flow physics.…”
mentioning
confidence: 99%
“…Many experimental investigations of aluminum droplet behavior in propellant plumes have been performed [4][5][6][7][8][9]. Optical techniques for measuring molten aluminum sizes and/or velocities have included point-wise phase Doppler anemometry [4], line-of-sight laser diffraction [5], videography [6], shadowgraphy [7], Schlieren [8], and holography [9].…”
mentioning
confidence: 99%